The Role of the Intestinal Context in the Generation of Tolerance and Inflammation - Bernardo Sgarbi Reis; Daniel Mucida (Clinical and Developmental Immunology)
The mucosal surface of the intestine alone forms the largest area exposed to exogenous antigens as well as the largest collection of lymphoid tissue in the body. The enormous amount of nonpathogenic and pathogenic bacteria and food-derived antigens that we are daily exposed sets an interesting challenge to the immune system: a protective immune activity must coexist with efficient regulatory mechanisms in order to maintain a health status of these organisms. This paper discusses how the immune system assimilates the perturbations from the environment without generating tissue damage.